Subversion of Cellular Autophagy Machinery by Hepatitis B Virus for Viral Envelopment - Li, Jianhua (American Society for Microbiology, 2011)
Autophagy is a conserved eukaryotic mechanism that mediates the removal of long-lived cytoplasmic macromolecules and damaged organelles via a lysosomal degradative pathway. Recently, a multitude of studies have reported that viral infections may have complex interconnections with the autophagic process. The findings reported here demonstrate that hepatitis B virus (HBV) can enhance the autophagic process in hepatoma cells without promoting protein degradation by the lysosome. Mutation analysis showed that HBV small surface protein (SHBs) was required for HBV to induce autophagy. The overexpression of SHBs was sufficient to induce autophagy. Furthermore, SHBs could trigger unfolded protein responses (UPR), and the blockage of UPR signaling pathways abrogated the SHB-induced lipidation of LC3-I. Meanwhile, the role of the autophagosome in HBV replication was examined. The inhibition of autophagosome formation by the autophagy inhibitor 3-methyladenine (3-MA) or small interfering RNA duplexes targeting the genes critical for autophagosome formation (Beclin1 and ATG5 genes) markedly inhibited HBV production, and the induction of autophagy by rapamycin or starvation greatly contributed to HBV production. Furthermore, evidence was provided to suggest that the autophagy machinery was required for HBV envelopment but not for the efficiency of HBV release. Finally, SHBs partially colocalized and interacted with autophagy protein LC3. Taken together, these results suggest that the host's autophagy machinery is activated during HBV infection to enhance HBV replication.